Preharvest sprouting of wheat effect on grain and flour quality - Beleia, Adelaide; Grossmann, Maria Victoria Eiras (Pesquisa Agropecuaria Brasileira, 2014)
- The effects of preharvest sprouting on the physical, chemical, milling, rheological and baking characteristics of wheat samples from Paraná and São Paulo, harvested in 1986, were examined. Degree of sprouting varied from zero to 46,1 percent. Increasing degree of germination caused decreasing hectoliter weight, flour extraction and increasing break flour production. Rheological properties of the doughs were also affected showing: higher tolerance index (farinograph) and extensibility (extensograph), while water absorption (farinograph), resistance to extention (extensograph) and peak viscosity (amilograph) decreased, with increasing levels of germination. Flours from wheats with lower degree of sprouting produced breads of acceptable quality, while flours from wheats with more than 20 percent sprouted kemels produced breads of much lower quality